KESEHATAN MENTAL DAN PSIKOTERAPI: PERSPEKTIF PSIKOLOGI ISLAM - Harsa Afifatur Rahmi (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2025)
This study examines mental health, psychopathology, as well as the techniques and procedures of Islamic psychotherapy using a literature review method. The findings indicate that mental health in Islam encompasses psychological, spiritual, and social well-being based on the Quran and Hadith. Islamic psychopathology is categorized into worldly disorders, such as anxiety and depression, and ukhrawi (spiritual) disorders related to moral and religious deviations. Islamic psychotherapy offers a faith-based approach, incorporating worship and ethical values to address mental disorders through techniques such as dhikr therapy, prayer, fasting, and the application of tauhid (monotheism), patience, gratitude, and reliance on Allah. The procedures of Islamic psychotherapy include preventive, curative, constructive, and rehabilitative approaches aimed at restoring psychological balance and guiding individuals back to their fitrah (natural state). By integrating Islamic principles with modern psychology, Islamic psychotherapy focuses not only on mental healing but also on fostering a harmonious and balanced personality in accordance with Islamic teachings.